Relationship between external and internal load measures in youth beach handball - Iannaccone, A.; Fusco, A.; Skarbalius, A.; Kniubaite, A.; Cortis, C.; Conte, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Assessing the relationship between external load (EL) and internal load (IL) in youth male beach handball players.